Electroconvulsive seizures lead to lipolytic‐induced gene expression changes in mediobasal hypothalamus and decreased white adipose tissue mass - Marika Takefusa; Yuki Kubo; Marie Ohno; Eri Segi‐Nishida (Wiley, 2021)
Abstract Aims Electroconvulsive seizure (ECS) therapy is highly effective in the treatment of several psychiatric disorders, including depression. Past studies have shown that the rodent model of ECS reveals the activation of multiple brain regions including the hypothalamus, suggesting that this method of brain stimulation broadly regulates central neuronal function, which results in peripheral function. The ventromedial nucleus of the hypothalamus (VMH) plays an important role in feeding and energy homeostasis. Our previous study showed that ECS increases the expression of anorexigenic factors in the VMH and has an anorexigenic effect in a mouse model. Since the VMH is also suggested to play a critical role in the peripheral lipid metabolism of white adipose tissue (WAT), we hypothesized that ECS alters lipid metabolism via activation of the VMH. Methods and Results Here, we demonstrate that repeated ECS suppresses the fat mass of epididymal WAT and significantly increases the expression levels of lipolytic and brown adipose tissue markers such as Adrb3, Hsl/Lipe, and Ppargc1a. In the VMH, ECS increased the expression of multiple genes, notably Bdnf, Adcyap1, and Crhr2, which are not only anorexigenic factors but are also modulators of lipid metabolism. Furthermore, gold‐thioglucose‐induced hypothalamic lesions affecting the VMH abolished the effect of ECS on the WAT, indicating that hypothalamus activation is required for the phenotypic changes seen in the epididymal WAT. Conclusion Our data demonstrates a new effect of ECS on the lipid metabolism of WAT via induction of hypothalamic activity involving the VMH.